Розробка конструкції пристрою хімічної постобробки виробів з пластмас - Тищенко, Д. В. (ХНУРЕ, 2020)
The given work is devoted to the analysis of methods of plastic cleaning, chemical processing device, principal scheme, writing code,manufacturing a make. The purpose of the work is to develop a device for chemical post processing of plastic products. The analysis of methods of postprocessing of parts is carried out. The process of chemical postprocessing is analyzed in detail, the mainparameters of the process of chemical post-processing are determined. The structural scheme and algorithm of the device of chemical postprocessing of plastic products have been developed. The issues of labor protection are considered. A layout of the device for chemical post-processing of plastic products is manufactured.
Keywords: хімічна постобробка; пластмаса; 3D друк